Technology, Taxation, and Corruption : Evidence from the Introduction of Electronic Tax Filing - Okunogbe, Oyebola (World Bank, Washington, DC, 2018)
Many e-government initiatives introduce technology to improve efficiency and avoid potential human bias. Electronic tax filing (e-filing) is an important example, as developing countries increasingly adopt online submission of tax declarations to replace in-person submission to tax officials. This paper examines the impact of e-filing on compliance costs, tax payments, and bribe payments using experimental variation and data from Tajikistan firms. Firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. In all, the results indicate that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable.